The Implementation Of Rudolf Butmann's Ontological Heurmenetics In The Context Of The Study Of Da'wah Texts And Communication - Fadhilah, Ninda Nurul; Milatul Zulfa; Muhammad Budi Harjono; M. Rais Ribha Rifqi Hakim; Naufal Tsabitulazmi (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
In the modern era marked by rationality and pluralism, religious messages often lose their existential depth when interpreted literally and rigidly. This condition calls for a new interpretive approach capable of unveiling the deeper meaning behind religious symbols and myths. Responding to this need, this study applies Rudolf Bultmann’s ontological hermeneutics to the field of Islamic da’wah and communication a domain that has rarely adopted an existential analytical framework. Using a qualitative descriptive method, the research employs demythologization to reinterpret symbolic and mythological expressions in the Qur’an, particularly the story of the Israelites cursed to become apes as narrated in Surah Al-A’raf verse 166. The findings reveal that the word ape is not merely a mythological expression but an existential metaphor for moral and spiritual degradation that occurs when humans betray divine values. The study concludes that applying Bultmann’s ontological hermeneutics offers a more reflective and relevant understanding of Qur’anic messages, bridging the gap between sacred revelation and the existential awareness of modern humanity.